2013
DOI: 10.1016/j.chemphys.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic and computational study of Al(III) complexes in cryolite melts: Effect of cation nature

Abstract: Graphical abstractHighlights► We investigate Li, Na and K cryolite melts by Raman spectroscopy and dft. ► A slight red shift of main Raman peaks is observed in the row Li+, Na+, K+. ► A decrease of the half-widths of peaks is observed in the same row. ► Fluoroaluminates and their complexation kinetics play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The ionic structures of the molten systems of alkali metal fluorides and aluminum fluoride have attracted significant interest from the research community. At present, the existence of AlF 6 3 − , AlF 5 2 − , and AlF 4 − complex ions have been proven by Raman spectroscopy [9][10][11][12][13][14] . It is acknowledged that the equilibria among the Al-F complex ions in molten systems exist as AlF 6 3 − = AlF 5 2 − + F − and AlF 5 2 − = AlF 4 − + F − .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The ionic structures of the molten systems of alkali metal fluorides and aluminum fluoride have attracted significant interest from the research community. At present, the existence of AlF 6 3 − , AlF 5 2 − , and AlF 4 − complex ions have been proven by Raman spectroscopy [9][10][11][12][13][14] . It is acknowledged that the equilibria among the Al-F complex ions in molten systems exist as AlF 6 3 − = AlF 5 2 − + F − and AlF 5 2 − = AlF 4 − + F − .…”
Section: Introductionmentioning
confidence: 98%
“…Simulation technology does not require physical experiments; thus, it is excellent for studying the ionic structures of molten salts. Molecular dynamic simulation and quantum chemical calculation are two conventional simulation techniques used to study the ionic structure of alkali metal fluorides and aluminum fluoride mixtures [14,[19][20][21] . The molecular dynamic results from the study by Bu čko and Šimko [22,23] showed that Al 2 F 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectra of molten fluoroaluminates were reinvestigated to certify the existence of [AlF 5 ] 2− clusters. [6] Lacassagne [7] observed 23 [8] In recent years, the molten binary MF-AlF 3 system has been extensively studied, [9][10][11] but the species in the melts is still a debatable issue. Since 1999, in situ high temperature 27 Al nuclear magnetic resonance (NMR) spectroscopy has been conjuncted with in situ high-temperature Raman spectroscopy to explore the structure of the molten NaF-AlF 3 system.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of cryolitic melts has been widely studied using different techniques such as cryoscopy, 2 molecular dynamics calculations 3 or Raman spectroscopy. [4][5][6][7] More recently, high temperature NMR spectroscopy has proven to be a powerful tool to determine in situ the structure of molten cryolitic systems. [8][9][10][11][12] Phosphorus is an important impurity element in electrolytic aluminium production, which comes from natural raw materials (primary and secondary alumina, and aluminium fluoride) and from fresh and recycled electrolyte.…”
Section: Introductionmentioning
confidence: 99%